Art and artifact - British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1971)
The programs talks about differentials between contemporary'fine' and'useful arts'
Converted into VHS 1/2 in.
Narrated by Arnold Kettle
Keywords: Art criticism; Antiquities